2017
DOI: 10.1002/iid3.191
|View full text |Cite
|
Sign up to set email alerts
|

A SNP uncoupling Mina expression from the TGFβ signaling pathway

Abstract: IntroductionMina is a JmjC family 2‐oxoglutarate oxygenase with pleiotropic roles in cell proliferation, cancer, T cell differentiation, pulmonary inflammation, and intestinal parasite expulsion. Although Mina expression varies according to cell‐type, developmental stage and activation state, its transcriptional regulation is poorly understood. Across inbred mouse strains, Mina protein level exhibits a bimodal distribution, correlating with inheritance of a biallelic haplotype block comprising 21 promoter/intr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 32 publications
0
7
0
Order By: Relevance
“…Furthermore, this finding also unraveled a forward feedback route between mdig and TGFβ. A recent comprehensive genetic study in BALB/C and C57BL/6 mice suggested that a single nucleotide polymorphism in the intron 1 region of mdig gene favors Smad3 binding, TGFβ responsiveness and mdig transcription 41.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, this finding also unraveled a forward feedback route between mdig and TGFβ. A recent comprehensive genetic study in BALB/C and C57BL/6 mice suggested that a single nucleotide polymorphism in the intron 1 region of mdig gene favors Smad3 binding, TGFβ responsiveness and mdig transcription 41.…”
Section: Discussionmentioning
confidence: 99%
“…The authors speculated that this may be mediated via an independent role for MINA in promoting T H 2 cytokine expression in antigen presenting cells. Others have proposed that the reduced airway disease in this model may be associated with a defective Th17 response [ 77 ]. If correct, this would suggest that the known role of MINA in Th17 differentiation (outlined above) may be dominant with respect to its role in T H 2 bias, at least in this particular disease.…”
Section: Minamentioning
confidence: 99%
“…Ribosomal oxygenase 2 (RIOX2/MINA) is a histone lysine demethylase important in TNFb signaling 63 and is associated with cell proliferation in a number of cancers. 64 , 65 It is increased in the LPS group, but not detected in DHA or the LPS + DHA group, again indicating a protective effect of DHA.…”
Section: Resultsmentioning
confidence: 99%
“…62 In the study by Yang et al, 62 LPSs were observed to alter secretion of EVs by the activation of ribosomal assembly and translation, which may play a role in the detrimental inflammatory responses in neurodegenerative diseases. Ribosomal oxygenase 2 (RIOX2/MINA) is a histone lysine demethylase important in TNFb signaling 63 and is associated with cell proliferation in a number of cancers. 64,65 It is increased in the LPS group, but not detected in DHA or the LPS + DHA group, again indicating a protective effect of DHA.…”
Section: Proteins Involved In the Ribosome Functionmentioning
confidence: 99%